BMO Spaces and John-Nirenberg Estimates for the Heisenberg Group Targets (Journal of Partial Differential Equations, 2003)
" In this paper, the BMO spaces for the Heisenberg group targets are studied. Some properties of the BMO spaces and the John-Nirenberg estimates are obtained."
Keywords: Heisenberg group; BMO spaces; John-Nirenberg estimates